Pengelolaan Sumber Daya Manusia Dalam Bisnis Hotel Studi komparasi di Hotel Duta Garden, Hotel Wisanti, Hotel Musafira dan Hotel Perwita Sari Yogyakarta - Diza Malida Ayunungsih; Asa Prihambodo; Ayu Yenny Susilowati; R. Sahedhy Noor SK (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2011)
This paper is the result of field research on human resource management in the hotel business. Observed variables: planning, recruitment, development and training, compensation, evaluation, and employees maintenance . Data collection using interviews, survey respondents were hotel owners and employees. The findings research include employees recruitment planning in Duta Garden Hotel, Wisanti Hotel, Musafira Hotel, and Perwita Sari Hotel, recruitment system to recruit employees to support the course of business Duta Garden Hotel, Hotel Wisanti, Musafira Hotel, and Perwita Sari Hotel, development and training undertaken by each hotel so that more potential employees, compensation for permanent employees every month or daily compensation for seasonal employees at Duta Garden Hotel, Musafira Hotel and Perwita Sari Hotel , assessment of employees on the basis of service and ways of working, and maintenance on each hotel in developing their employees. Our recommendation for each aspect are discussed on paper. Keywords: human resources management, hotel business